MIGRASI MANUSIA DI ASIA PASIFIK DAN IMPLIKASINYA - Poltak Partogi Nainggolan (Sekretariat Jenderal DPR RI, 2014)
Current global situation is marked by people migration involving large numbers non-state actors, particularly in Asia-Pacific. People’s activities across regions in various forms, i.e. the flows of legal and illegal migrants, migrant workers, refugees, and radical groups, and cases of people smugging etc, have brought about further implications to state-relations and stability in the region. This essay is part of a qualitative research report which uses writing sources and in-depth interviews. Its analysis reveals a more intensive activities of non-state actors which threat states stability and their relations each other.